Suitability of various substrates for cultivation of Pleurotus florida and P. sajor-caju in Andaman and Nicobar Islands - Kumar, Krishan; Bhagat, Someshwar; Birah, Ajanta; Srivastava, R C (Mushroom Research, 2015)
Please see the full text